2006
DOI: 10.1002/app.23959
|View full text |Cite
|
Sign up to set email alerts
|

Nanoscratch testing to assess the fiber adhesion of short‐carbon‐fiber composites

Abstract: In a composite material, the degree of adhesion between the fiber and the matrix plays an important role in the overall performance of the material. Because the load between the fiber and the matrix is realized throughout the interphase region material, a lot of effort has gone into characterizing the strength of the interphase. In this study, nanoscratch tests on the composite samples were used to provide a relative measure of adhesion in different composite materials. Carbon-filled nylon 6,6 and polycarbonat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…Table IX shows the results for the crest factor, comparing the penetration of the indenter into composites containing 20 wt % in Vectra A950RX LCP and in the polypropylene matrix used in this project 61. Previous research62 has shown that the normalized crest factor (ratio of the composite crest factor to the polymer crest factor) can be used as a measure to compare the relative degree of adhesion between different composites having the same matrix but different types of fillers. A higher normalized crest factor is indicative of a resistance of the composite to scratching, due to better filler/matrix adhesion.…”
Section: Resultsmentioning
confidence: 99%
“…Table IX shows the results for the crest factor, comparing the penetration of the indenter into composites containing 20 wt % in Vectra A950RX LCP and in the polypropylene matrix used in this project 61. Previous research62 has shown that the normalized crest factor (ratio of the composite crest factor to the polymer crest factor) can be used as a measure to compare the relative degree of adhesion between different composites having the same matrix but different types of fillers. A higher normalized crest factor is indicative of a resistance of the composite to scratching, due to better filler/matrix adhesion.…”
Section: Resultsmentioning
confidence: 99%
“…The critical loads can also be confirmed and collated with observations from a built‐in optical microscope or examined by scanning electronic microscopy and atomic force microscopy. The critical load data is used to quantify the fracture thresholds, and adhesive properties of different coating‐substrate combinations 19, 20…”
Section: Resultsmentioning
confidence: 99%
“…This increase of counterbody roughness was also reported due to hard fillers' abrasion [25] or tribochemical oxidation. [28] In the present study, the friction stability is quantified by using the crest factor, which quantifies the amplitude of spikes in friction relative to its root-mean-square value as defined in the work of King et al [29] The lower the crest factor value is, the smoother the sliding process proceeds. Composite coatings C2, C3, and C4 did not withstand test but failed after about 200 cycles of sliding and are not further studied in the following.…”
Section: Mechanisms Of Tribological Performancementioning
confidence: 99%